2014
DOI: 10.1002/jmri.24800
|View full text |Cite
|
Sign up to set email alerts
|

3D ECG- and respiratory-gated non-contrast-enhanced (CE) perfusion MRI for postoperative lung function prediction in non-small-cell lung cancer patients: A comparison with thin-section quantitative computed tomography, dynamic CE-perfusion MRI, and perfus

Abstract: Non-CE-perfusion MRI may be able to predict postoperative lung function more accurately than qualitatively assessed MDCT and perfusion scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…The tests broadly involve estimation of how much lung tissue is to be removed with or without estimation of the functionality of the lung. CT volume tests used the volume of the lobe to be resected as measured on CT relative to the total lung volumes as the proportion of function expected to be lost [13]. CT-VD tests take into account the density of lung tissue in Hounsfield units, a measure of emphysematous destruction, in addition to lung volumes to define functional lung tissue [13], [14], [15], [16], [17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The tests broadly involve estimation of how much lung tissue is to be removed with or without estimation of the functionality of the lung. CT volume tests used the volume of the lobe to be resected as measured on CT relative to the total lung volumes as the proportion of function expected to be lost [13]. CT-VD tests take into account the density of lung tissue in Hounsfield units, a measure of emphysematous destruction, in addition to lung volumes to define functional lung tissue [13], [14], [15], [16], [17].…”
Section: Resultsmentioning
confidence: 99%
“…CT volume tests used the volume of the lobe to be resected as measured on CT relative to the total lung volumes as the proportion of function expected to be lost [13]. CT-VD tests take into account the density of lung tissue in Hounsfield units, a measure of emphysematous destruction, in addition to lung volumes to define functional lung tissue [13], [14], [15], [16], [17]. CT density masks to define functional lung tissue varied between − 1024 and − 910 for the lower limit − 650 and − 500 for the upper limit [13], [14], [15], [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 ] The dynamic perfusion MRI has shown good predictive capability, but it is expensive, technically difficult, and affected by motion and severe susceptibility artefacts. [ 13 ] Radionuclide perfusion scintigraphy is easily available, cost-effective, can noninvasively evaluate the regional lung function and is the most commonly used method to predict postoperative FEV1. [ 7 ] Many studies have shown good correlation between the actual postoperative FEV1 and PPO FEV1 obtained by lung perfusion scintigraphy.…”
Section: Introductionmentioning
confidence: 99%